Studi Fitokimia Dan Farmakologi Morinda Citrifolia Dalam Terapi Kanker: Artikel Review - Maria Fransiska Silviani Derosari; Niken Rahmita Khairani; Safanda Tiara Fitri; Miya Hartini Nur Wakhid; Ewalde Yovita Bria; Magdalena Kasmin Belaon Lebuan; Aprilia Puji Astuti; Maulidiyah Cholifah; Agustinus Alfred Seran; Ivan Charles S.Klau; Arista Wahyu Ningsih (Lembaga Pengembangan Kinerja Dosen, 2024)
Morinda citrifolia (noni) is a plant that has attracted attention in research as a source of compounds with anti-cancer potential. The aim of this comprehensive understanding is to analyze various studies that have been carried out to investigate the ability of Morinda citrifolia in cancer therapy. The research method involved a qualitative literature study, where we collected ten research articles that had been conducted on various types of cancer cells and the compounds contained in Morinda citrifolia. Research results show that Morinda citrifolia contains a variety of compounds such as anthraquinones, scopoletin, quercetin, and others, which have shown promising anti-cancer activity. In addition, in-silico research also identifies compounds that have the potential to influence key molecular targets in cancer growth pathways. Research results show a variety of anticancer activities associated with these compounds, including their ability to inhibit cancer cell growth, induce apoptosis, reduce oxidative stress, and inhibit cancer cell movement. In several studies, compounds such as morindone, scopoletin, and quercetin have shown promising anticancer activity, especially in certain cancer cell models. In conclusion, Morinda citrifolia shows potential as a source of interesting anti-cancer compounds, and further research is expected to help better understand the potential benefits of this plant in cancer therapy. In this context, further clinical research is needed to validate the efficacy and safety of using Morinda citrifolia in cancer therapy in humans.